A unified representation of the temperature dependences of soil microbial growth and respiration - Brangarí, Albert C. ; 0000-0002-1212-8875; Rousk, Johannes ; 0000-0002-4985-7262 (Communications Earth and Environment, 2025)
Temperature impacts on microbiological processes are crucial for soil biogeochemistry and ecosystem functioning, yet existing models either fail to capture microbial temperature dependences across the full biokinetic range or risk overparameterization. Here we present the “Dual-Kinetics Ratkowsky” model (Ratkowsky DK), which simultaneously describes temperature dependences of microbial growth and respiration. Compared to established models (Arrhenius, Ratkowsky, MMRT, and MMRT-2S), Ratkowsky DK showed superior performance and parsimony when applied to soils along a climate gradient, with strong implications for estimating soil carbon stock changes. Although empirically derived, the model provides reliable estimates of microbial thermal traits and climate responsiveness, reflecting warm- and cold-shifted adaptations. It also offers a biological interpretation whereby temperature-driven cell death fuels respiration beyond a threshold, explaining the decoupling between anabolism and catabolism. Ratkowsky DK represents a promising tool for advancing our understanding of microbial and biogeochemical responses to climate and implementation of ecology into Earth system representations. (Figure presented.)